The Development of Chemical Practice Guidebook Colloid System-Based Integrated Contextual Character Values - Ester Manalu; Saronom Silaban; Ramlan Silaban; Wesly Hutabarat (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract- This research is a development that aims to develop guiding chemistry lab contextually based integrated character values, knowing improving student learning outcomes in terms of cognitive and determine student learning outcomes in terms of affective and psychomotor using guiding chemistry laboratory that has been developed , The study was conducted in Cahaya Medan high school. Samples are two classes were taken by purposive sumpling using PPKBK experimental class I and class II experiment using PP available in school study instrument is a rubric validation, test and observation sheet. Research began on analytical chemistry lab at the school guidance, development, validation, revision and test laboratory guides that have been developed. The product of research is (1) based on the analysis of chemical PP book in colloidal system materials publisher grants, Pudak Scientific, Duta Nusantara and Laskar Aksara is not in accordance with BSNP, (2) based PPKBK BSNP integrated character values is more valid than the PP chemicals used in schools, 93) there is a difference in improving student learning outcomes in terms of cognitive, that learned to use the integrated PPKBK character values of 0.73, while that learned with chemicals used PP 0,63 school, (4) there are differences in student learning outcomes in terms of psychomotor aspect that learned to use PPKBK integrated character values at 91 and that learned with PP chemicals used school at 85, while in terms of affective aspects that learned to use PPKBK integrated character values of 92 and PP with chemicals schools at 81. Keywords: Development of practical guidance, based contextual character values, the colloid system